From Introduced to Invasive and Iconic: An aquaculture oyster (Crassostrea gigas) and social-ecological resilience in Puget Sound - Hauptfeld, Kathrin Simone (My University, 2013)
The resilience framework is increasingly used to understand the dynamics of sustainability in coupled social and ecological systems. Resilient ecological systems exhibit high levels of diversity, including species and habitat diversity, and redundancy, all of which are thought to help maintain the system within a domain of attraction. Numerous studies demonstrate the threat posed to natural systems by the introduction of invasive species on a global scale. Over the past century, biological invasion has caused changes in biological diversity and alterations to the structure and function of ecosystems. In Puget Sound, the non-native Pacific oyster (Crassostrea gigas) has been used as a commercial aquaculture species for over a century, despite increasing evidence that its spread threatens ecological resilience of the nearshore system. Interestingly, recent changes in ocean conditions that lessen the invasion threat have been met with alarm in Washington, as they jeopardize the social resilience built on the culture of Pacific oysters. In this case study, I discuss conflicts between social and ecological resilience, and the values that drive those conflicts. I then discuss social adaptation strategies as options to retain social-ecological resilience within the system.
Thesis (Master's)--University of Washington, 2013
Keywords: Aquaculture; Crassostrea gigas; Puget Sound; Social-ecological resilience; Natural resource management; Ecology; marine affairs